2002
DOI: 10.1081/ese-100108483
|View full text |Cite
|
Sign up to set email alerts
|

ROOT ZONE TEMPERATURE AFFECTS THE PHYTOEXTRACTION OF Ba, Cl, Sn, Pt, AND Rb USING POTATO PLANTS (SOLANUM TUBEROSUML. VAR. SPUNTA) IN THE FIELD

Abstract: Three consecutive years of field experiments were conducted to investigate how different root-zone temperatures, manipulated by using different mulches, affect the phytoextraction of Ba, Cl, Sn, Pt and Rb in different organs of potato plants (roots, tubers, stems and leaves). Four different plastic covers were used (T1: transparent polyethylene; T2: white polyethylene; T3: white and black coextruded polyethylene, and T4: black polyethylene), using uncovered plants as control (T0). The different treatments had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…1). Similar results were also reported for potato (Baghour et al 2001(Baghour et al , 2002a(Baghour et al , 2002b(Baghour et al , 2002c(Baghour et al , 2003, Brassica napus (Ye et al 2006) and tropical cucurbitaceous plants (Zhang et al 2008): within the RZT range of 20-27 C, the total biomass increased in plants, while outside this range the dry weight fell. Effect of low RZT has been previously emphasized; Engels and Marschner (1990) found that low root temperatures not only delayed root growth but also reduced the shoot growth of corn plants.…”
Section: Rzt and Plant Growthsupporting
confidence: 87%
See 2 more Smart Citations
“…1). Similar results were also reported for potato (Baghour et al 2001(Baghour et al , 2002a(Baghour et al , 2002b(Baghour et al , 2002c(Baghour et al , 2003, Brassica napus (Ye et al 2006) and tropical cucurbitaceous plants (Zhang et al 2008): within the RZT range of 20-27 C, the total biomass increased in plants, while outside this range the dry weight fell. Effect of low RZT has been previously emphasized; Engels and Marschner (1990) found that low root temperatures not only delayed root growth but also reduced the shoot growth of corn plants.…”
Section: Rzt and Plant Growthsupporting
confidence: 87%
“…Baghour and co-workers demonstrated that 23-27 C soil temperature was optimum for the uptake of most essential and some non-essential elements such as aluminum (Al), As, barium (Ba), Cd, nickel (Ni) and lead (Pb) (Baghour et al 2001(Baghour et al , 2002a(Baghour et al , 2002b(Baghour et al , 2002c(Baghour et al , 2003. These studies also showed that RZT < 20 C, considered sub-optimal for most plants (Zhang et al 2008;Adebooye et al 2010), exacerbates growth as well as nutrient uptake.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation